Hierarchical Porous Framework of Si‐Based Electrodes for Minimal Volumetric Expansion. (13th March 2014) - Piper, Daniela Molina; Woo, Jae Ha; Son, Seoung‐Bum; Kim, Seul Cham; Oh, Kyu Hwan; Lee, Se‐Hee
<x xml:space="preserve">Abstract</x> A tunable hierarchical porous framework is fabricated to house the volumetric changes outputted by Si. The nSi@cPAN/cPAN electrodes only expand by 14.3% at full initial lithiation and remain within 23% expansion from its uncycled state after 20 cycles with remarkable cycling stability and high coulombic efficiencies in excess of 99.5%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>